The inverse relationship between fatness and bone mineral content is mediated by the adolescent appendicular skeletal muscle mass index: The Cogni-Action Project - Cristi-Montero, Carlos; Peña-Jorquera, Humberto; Landaeta-Díaz, Leslie; Mello, Julio B.; Araya-Quintanilla, Felipe; Brand, Caroline; Reuter, Cézane; Jorquera, Carlos; Ferrari, Gerson (Frontiers in Nutrition, 2022)
Background Excessive adiposity tissue plays a detrimental influence on bone health during childhood affecting future diseases of bone fragility such as osteoporosis. However, little is known about how adolescents’ appendicular skeletal muscle mass index (ASMI) may mediate the relation between fatness and bone mineral content (BMC). Methods The sample comprised 1,296 adolescents (50% girls) aged 10-14. A principal component analysis was performed to obtain a factor composed of four fatness indicators a) neck circumference, b) kilograms of fat, c) visceral fat area, and d) waist-to-height ratio. The BMC, kilograms of fat, visceral fat area, and appendicular skeletal muscle mass were obtained by a multi-frequency bioelectrical impedance analyzer. ASMI was calculated as the appendicular skeletal muscle mass divided by height squared (kg/m2). A mediation analysis was performed adjusting by age, sex, maturation, socioeconomic status, and adolescents’ body weight. Results The fatness factor explained 71.5% of the proportion variance. Fatness was inversely associated with the ASMI and BMC, while the ASMI was positively related to BMC. Overall, the inverse relationship between fatness and BMC was partially mediated by the adolescents’ ASMI (29,9%, indirect effect: B= -0.050, 95%CI -0.080 to -0.024), being higher in girls than in boys (32.8% vs. 29.9%). Conclusions This finding highlighted the relevance of promoting healthy adolescent habits to reduce fatness and improve muscle mass. Moreover, embossing the central role of ASMI mediating the inverse association between fatness and BMC in female and male adolescents. Public health strategies should promote bone health in childhood, reducing the incidence of early osteopenia and osteoporosis.